(untitled) (Community Based Medical Journal, 2021)
Health research is a moral duty because it is the foundation for evidence-based care by all health care practitioners. Hence, paediatric research is essential for improving health outcomes of children. Waiting for adult studies before conducting paediatric studies may prolong the denial of effective treatment for children. The CIOMS and other guidelines clearly allow research procedures that involve a low degree of risk. However, the critical need for pediatric research on drugs and biological products underscores the responsibility to ensure that children are enrolled in clinical research that is both scientifically necessary and ethically sound. Even in a resource poor setting of a developing country like Bangladesh, the things that should be taken under considerations are the status of children as a vulnerable population; the appropriate balance of risk and potential benefit in research; ethical considerations underlying study design, including clinical equipoise, placebo controls, and non-inferiority designs; the use of data; compensation; and parental permission and child assent where applicable to participate in research. Such ethical dilemmas are more evident in paediatric research especially when a collaborative research is done by a developed country in a developing country setting. It is the role of the health policy makers, and community of paediatric physicians, nurses, and caregivers to advocate not only for more research for children but also to ensure that the research conducted is of the highest quality from ethical viewpoint. CBMJ 2020 July: Vol. 09 No. 02 P: 54-58